Usage of adapted spelling of names from foreign modern languages in the Serbian daily press - Totaj, Luka (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
In this paper, we will present the results of the content analysis that we used when examining the usage of transcription in the Serbian daily newspapers that publishing nationally, videlicet in the sections: “Politics”, “World” and “Sport”. The data was collected in the penultimate week of June 2021. Textual analysis and quantitative content analysis were used in the study. Our aim was to determine the frequency of transcription errors in the Serbian press. Anthroponyms from those languages ​​whose transcription is explained in the Orthography Book of Serbian were our analytical unit. In this paper, we introduced a new communicative-linguistic term “transcriptional fallacy” which was also a segment in the analysis. The obtained results tell us that the frequency of transcription errors is on a medium level, which leans more towards a bad than a good grade. Transcription errors are most often made due to an uncritical imitation of the original language’s script, although the other two fallacies are also frequent.
Keywords: transcription; orthography; the Orthography Book of Serbian [=Pravopis srpskoga jezika]; literary language; language culture; print media; the Serbian language